2021
DOI: 10.2217/epi-2020-0414
|View full text |Cite
|
Sign up to set email alerts
|

ARID1 Proteins: from Transcriptional and Post-Translational Regulation to Carcinogenesis and Potential Therapeutics

Abstract: The ARID1 proteins are mutually exclusive subunits of the BRG1/BRM-associated factor (BAF) complexes that play an important role in chromatin remodeling and regulate many fundamental cell functions. The role of ARID1s is well defined as a tumor-suppressive. The cancer cells evolve different mechanisms to downregulate ARID1s and inactivate their functions. ARID1s are frequently mutated in human cancer. The recent findings of ARID1A/B downregulation at transcriptional and translational levels along with their lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Cox regression analyses indicated that the risk score of the signature could be a powerful indicator of GC patient clinical outcome (Figures 7(e) and 7(f) ). Interestingly, TTN [ 21 ], TP53 [ 22 ], MUC16 [ 23 ], and ARID1A [ 24 ] were the top mutations in both cohorts and were involved in various biological processes. In addition, the frequencies of all mutated genes were higher in the high-risk group (96.74%) ( Figure 8(a) ) than in the low-risk group (84.75%) ( Figure 8(b) ), suggesting that somatic mutation was positively correlated with risk scores.…”
Section: Resultsmentioning
confidence: 99%
“…Cox regression analyses indicated that the risk score of the signature could be a powerful indicator of GC patient clinical outcome (Figures 7(e) and 7(f) ). Interestingly, TTN [ 21 ], TP53 [ 22 ], MUC16 [ 23 ], and ARID1A [ 24 ] were the top mutations in both cohorts and were involved in various biological processes. In addition, the frequencies of all mutated genes were higher in the high-risk group (96.74%) ( Figure 8(a) ) than in the low-risk group (84.75%) ( Figure 8(b) ), suggesting that somatic mutation was positively correlated with risk scores.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ARID1A in cancer can be regulated by way of promotor methylation or post-transcriptional modification. 15,41 In addition, there is also a report that ARID1A can be regulated by EBVencoded miRNA in EBV-positive GCs. 42 Due to the large number of the sample of this study, there are limitations in analyzing mutation and epigenetic profiles for every tumors; however, we expect that decreased ARID1A expression is associated with non-mutational alteration of ARI-D1A and results of this study support the supposition.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, post-translational changes lead to the loss of the ARID1A protein. Importantly, ARID1A inactivation is associated with poor outcomes and reduced chemosensitivity in many tumor types, including clear-cell OCs [2,377,383,[387][388][389].…”
Section: Arid1amentioning
confidence: 99%